Dīwān-i ghazaliyāt-i Asīr-i Shahristānī - Shahristānī, Asīr, (Miras Maktoob, ISBN: 9789004365452., 2019)
Persian poetry of the pre-modern era is divided into three successive styles, each belonging to a different period: Khurāsānī, ʿIrāqī and Hindī. The Hindī style's name comes from Safavid times, during which it developed; poets no longer enjoyed the shah's patronage, so that many of them went to India, where Persian poetry had flourished from Ghaznavid times (11th-12th cent.). The Hindī style is often regarded as being of a lesser kind than the Khurāsānī or ʿIrāqī ones, but has the merit of having ended the decline that Persian poetry was suffering from at the time and also, by its accessible language and subject matter, of having brought poetry within reach of the ordinary man. The poems of Asīr Shahristānī (11th/17th cent.), whose ghazal s are published here, are written in the Hindī style. Popular in India, even if he never went there, their appreciation in Iran has varied.